2006
DOI: 10.1097/01.ico.0000183531.25201.0d
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polyurethane Minisponges to Collect Human Tear Fluid

Abstract: Tear collection by absorbing polyurethane minisponges is highly advantageous in efficiency (recovery) and reproducibility (invariant electrophoretic polypeptide profiles). Tear donor comfort, simultaneous bilateral collection, and collections from several donors at once are additional major advantages of this collection method in studies involving single subjects and populations in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…A theoretical advantage of the capillaries compared to the other methods is that it can collect the pure tear. Nevertheless, López-Cisternas et al [26] have demonstrated that the results of the electrophoretic protein profiles of tear samples were indistinguishable between polyurethane foam cylinders (similar material to polyvinyl acetal) and to the one obtained with capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical advantage of the capillaries compared to the other methods is that it can collect the pure tear. Nevertheless, López-Cisternas et al [26] have demonstrated that the results of the electrophoretic protein profiles of tear samples were indistinguishable between polyurethane foam cylinders (similar material to polyvinyl acetal) and to the one obtained with capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Microsponges were then centrifuged to dryness at 13,000 rpm for 3 minutes to recover tears [4]. The amount of fluid recovered was determined as previously described [12]. Briefly, it was obtained by weighing the sponge and the tube after absorption and centrifugation steps, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the tear protein pattern as obtained by varying concentrations of polyacrylamide gels, and compared with the results of other published studies [19,20,24,32,33]. We identified a commercially available protein standard marker, SBTI, with a molecular weight of 20.1 kD, that did not overlap with any of the major tear protein bands in the 15% gel (Fig.…”
Section: The Choice Of the Internal Standard Proteinmentioning
confidence: 98%